2008
DOI: 10.1080/01443610802149806
|View full text |Cite
|
Sign up to set email alerts
|

The role of single serum progesterone measurement in conjunction with βhCG in the management of suspected ectopic pregnancy

Abstract: Our aim was to test the use of single serum progesterone measurement together with beta hCG in the management of women with pregnancy of unknown location. This was a retrospective study of 126 patients presenting with a clinical picture suggestive of ectopic pregnancy, when ultrasound examination was inconclusive. All the patients had serum progesterone level measured by radioimmunoassay in conjunction with beta hCG. The study showed that a protocol combining single serum progesterone measurement and beta hCG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The strategy in the USA is to follow serial serum hCG concentrations until these levels deviate from what is expected for a potential viable gestation or miscarriage (33-35). Others have advocated the use of serum progesterone as an adjuvant in the diagnostic process (17,26,36,37). Condous et al .…”
Section: Resultsmentioning
confidence: 99%
“…The strategy in the USA is to follow serial serum hCG concentrations until these levels deviate from what is expected for a potential viable gestation or miscarriage (33-35). Others have advocated the use of serum progesterone as an adjuvant in the diagnostic process (17,26,36,37). Condous et al .…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies included women with pain or bleeding alone,16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 and seven studies included women with pain or bleeding and inconclusive ultrasound diagnosis 3435 36 37 38 39 40 The supplementary (web extra) table shows the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The thresholds of progesterone used ranged from 3.2 to 11 ng/mL (10 to 35 nmol/L); the most commonly used threshold was 5 ng/mL (16 nmol/L), which was used in three studies 3437 38 Figures 3 and 4 show the estimated sensitivities and specificities when using the single progesterone measurement test for differentiating between viable and non-viable pregnancies, which includes both miscarriages and ectopic pregnancies. After meta-analysis of five studies (1998 participants) with similar cut-off values (3.2 to 6 ng/mL),34 35 36 37 38 we found that a single progesterone measurement predicted a non-viable pregnancy with pooled sensitivity of 74.6% (95% confidence interval 50.6% to 89.4%), specificity of 98.4% (90.9% to 99.7%), positive likelihood ratio of 45 (7.1 to 289), and negative likelihood ratio of 0.26 (0.12 to 0.57).…”
Section: Resultsmentioning
confidence: 99%
“…Our research consortium has published on logistic regression models such as the ‘M4 model’ that also use the predictive power of hCG. The utility of other clinically used serum biomarkers such as progesterone, novel serum biomarkers, clinical markers such as the amount of vaginal bleeding experienced and ultrasound‐based markers such as the endometrial thickness have also been evaluated. There is a lack of clarity for clinicians on which protocol is best and therefore a great deal of heterogeneity in how women with a PUL are managed.…”
Section: Introductionmentioning
confidence: 99%